Intersectionality in youth climate activism as educational practice: political, pragmatic, and pedagogical dimensions - Garcia, Ana; Rebelo, Dora; Diógenes-Lima, Juliana; Fernandes-Jesus, Maria; Malafaia, Carla (Frontiers in Education, 2025)
Youth climate movements have increasingly adopted an intersectional approach to activism, highlighting how diverse social categories (inter alia, race, gender, social class, sexuality) intersect with power structures and systems of oppression. This article explores the educational value of practices of intersectionality as they unfold in activists’ everyday lives, both within the climate movement and in its relationship with other movements. Drawing on multi-sited ethnographic data from young climate activists belonging to the School Strike for Climate chapters in Portugal’s two largest cities (Porto and Lisbon), we account for both private and public activist events—such as activists’ meetings, school occupations, and protest actions—and the connections with other activist causes, including feminist, anti-fascist, pro-housing, and LGBTQI+ rights. We show that intersectionality in youth collective action translates into: (i) a political commitment to anchor the climate struggle in systemic injustices that affect minoritized groups and non-normative identities, and (ii) a pragmatic strategy to uphold the public relevance and reach of youth climate mobilization. Simultaneously, our data reveal how the intersectional framework in climate activism translates into informal educational experiences that are significant for political socialization and collective learning, challenging conventional pedagogical processes and hegemonic education systems. This article contributes to expanding traditional notions of education, emphasizing the importance of climate activism as localized political spheres that promote opportunities for participatory learning, aimed at co-constructing just, democratic, and inclusive futures.